Emerging metallic systems for additive manufacturing : in-situ alloying and multi-metal processing in laser powder bed fusion - Sing, Swee Leong (2021)
While significant progress has been made in understanding laser powder bed fusion (L-PBF) as well as the fabrication of various materials using this technology, there is still limited adoption in the industry. One of the key obstacles identified is the lack of materials that can truly manufacture functional parts directly with L-PBF. This paper covers the emerging research on in-situ alloying and multi-metal processing. A comprehensive overview of the underlying scientific topics behind them is presented. The current state of research and progress from different perspectives (the materials and L-PBF processing parameters) are reviewed in order to provide a basis for follow-up research and development of these approaches. Defects, especially those associated with these two material processing routes, are also elucidated by discussing the mechanisms of their formation, including the main influencing factors, and the tendency for them to occur. Future research trends and potential topics are illustrated. The final part of this paper summarizes findings from this review and outlines the possibility of in-situ alloying and multi-metal processing using L-PBF.